The Female Journalist Leadership and Gender Mainstreaming in Jamberita.com Media in Jambi - A Arfan (HUMANISMA : Journal of Gender Studies, 2022)
The background of this research was the social fact about the female journalist as company leader as well as chief editor in Jamberita.com media. The majority of chief editors of local media were dominated by male. The purpose of this study was to find out the forms of gender mainstreaming in Jamberita.com media because of the emergence of gender mainstreaming concept among its journalists and to examine the role of female leader in journalism of Jamberita.com media. This study used qualitative method by conducting observation for 10 days in July 2021 and interviewing three informants who were the chief editor and the journalists of Jamberita.com media. The results of this study found the forms of gender mainstreaming in Jamberita.com media through the same assignments and responsibilities. The women got the same opportunities in producing news according to their respective posts. The concept of gender mainstreaming in Jamberita.com media emerged as a strategy to achieve justice in the world of journalism. The female leader in Jamberita.com media in Jambi has been able to carry out her responsibilities by taking an active role in organizational activities and being able to provide work motivation to staff members well so that some fundamental things affected her position as the chief editor of Jamberita.com media, in terms of social values, social status, communication, education, and work experience. This study has implications for the important role of women in the world of journalism and opens up the chances for other researches that connect gender and journalism.Penelitian ini dilatarbelakangi oleh fakta sosial jurnalis perempuan sebagai pemimpin perusahaan sekaligus pemimpin redaksi di media Jamberita.com. Pemimpin redaksi media lokal mayoritas didominan laki-laki. Tujuan penelitian mengetahui bentuk-bentuk pengarusutamaan gender di Jamberita.com, sebab munculnya konsep pengarusutamaan gender di kalangan jurnalisnya dan meneliti peran pemimpin perempuan dalam ruang jurnalisme Media Jamberita.com. Penelitian ini menggunakan pendekatan kualitatif, observasi dilakukan selama 10 hari pada bulan Juli 2021 dan wawancara dengan tiga orang informan yang merupakan pemimpin redaksi dan wartawan media Jamberita.com. Hasil penelitian ini menemukan bentuk-bentuk pengarusutamaan gender di Jamberita.com melalui pemberian tugas dan tanggungjawab yang sama, perempuan mendapat kesempatan yang sama dalam memproduksi berita sesuai dengan posnya masing-masing. Adapun konsep pengarusutamaan gender di Jamberita.com muncul sebagai strategi untuk mencapai keadilan dalam dunia kerja jurnalistik. Sementara pemimpin perempuan di Media Jamberita.com kota Jambi telah mampu menjalankan tanggungjawabnya dengan berperan aktif dalam kegiatan organisasi, mampu memberikan motivasi kerja kepada bawahan denganbaik, sehingga beberapa hal fundamental mempengaruhi posisinya sebagai ketua redaksi media Jamberita.com, dari segi nilai-nilaisosial, status sosial, komunikasi, pendidikan, dan pengalaman kerja. Penelitian ini berimplikasi kepada peran penting perempuan dalam dunia jurnalistik dan akan membuka ruang bagi penelitian lain yang menghubungkan gender dan jurnalisme.